Pengaruh Dividen Per Saham dan Laba Per Saham Terhadap Harga Saham: Studi Empiris Pada Perusahaan Indeks Kompas 100 Yang Terdaftar di Bursa Efek Indonesia Tahun 2016 - 2018 - Rachmawati, Fauziyah Tri; Sumiati, Ati; Fauzi, Achmad (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2020)
This study aims to determine the effect of dividend per share and earnings per share on stock prices on the Compass 100 Index companies listed on the Indonesia Stock Exchange in 2016 – 2018 both partially and simultaneously. The method used is a quantitative method with descriptive statistical analysis. Affordable population that meets the criteria of 55 companies with a sample of 48 companies obtained with a purposive sampling. The analysis of this study uses panel data regression with fixed effect model specifications. The results of this study indicate (1) dividend per share partially influences changes in stock prices with a significance value of 0.0427 < 0.05 (2) earnings per share partially does not affect the changes in stock prices with a significance value of 0.8831 > 0.05 (3) dividend per share and earnings per share simultaneously affect changes in stock prices with a significance value of 0.000000 < 0.05. And has a correlation coefficient with a value of 0.973261 with a high classification and a coefficient of determination of 95.93%.